2019
DOI: 10.1097/olq.0000000000000906
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Repeat Chlamydial Infections Among Young Women—Louisiana, 2000–2015

Abstract: Repeat chlamydial infections were common, especially among young black women. The true number is likely higher because surveillance data only count infections that were detected and reported. Comprehensive prevention strategies are needed to address high rates of repeat chlamydial infections among women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…early detection, treatment and prevention for repeat infections, C. trachomatis infections are rising. 21 The ongoing unmet need and 'mounting pressure' to develop chlamydia vaccines is visible in the patent landscape and is especially reflected in patenting activity for interventions in humans. 22 This study found clear technical and clinical differences between innovation efforts in the human and veterinary field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…early detection, treatment and prevention for repeat infections, C. trachomatis infections are rising. 21 The ongoing unmet need and 'mounting pressure' to develop chlamydia vaccines is visible in the patent landscape and is especially reflected in patenting activity for interventions in humans. 22 This study found clear technical and clinical differences between innovation efforts in the human and veterinary field.…”
Section: Discussionmentioning
confidence: 99%
“…All this indicates a high interest or high sense of urgency to solve the unmet need in the US. 21 In contrast, most veterinary vaccines are applied for by Chinese and Russian applicants. This interest by Chinese applicants can be explained by the economic burden that veterinary chlamydia serovars pose on Chinese livestock.…”
Section: Discussionmentioning
confidence: 99%
“…12,34 Rates of recurrent infection in nonpregnant women average 14%, and predictors of recurrence include age of <20 years and black race. 4,15,35 The current study shows that gonorrhea and syphilis coinfection in pregnancy is independently associated with persistent or recurrent chlamydia. This is consistent with studies in nonpregnant women.…”
Section: Resultsmentioning
confidence: 51%
“…1 Women between the ages of 15 and 24 years and women who reside in the southeastern United States, where the case rate is 744 cases per 100,000 persons, are disproportionally affected by chlamydia. 1 - 4 Untreated chlamydia in pregnancy has been associated with preterm delivery and low birthweight (LBW) infants. 5 - 9 Infection in women is usually asymptomatic, and timely screening and treatment in pregnancy can prevent adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Rescreening fluctuated year to year but the overall trend was consistently suboptimal. The findings of higher positivity at rescreening compared with initial screening might be due to numerous factors, including high community prevalence, re-exposure to untreated sexual partners, and treatment compliance issues ( 33 , 34 ). Rescreening also might have been focused on the adolescent and young females who were identified as having a higher risk for reinfection, thus overestimating the prevalence of reinfection.…”
Section: Discussionmentioning
confidence: 99%